KAJIAN PERANCANGAN PASAR MILENIAL: PASAR YANG MERESPON PERILAKU MILENIAL - Rudy Lim; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2019)
The market began to lose its physical form due to the emergence of the online market, which was caused by the behavior of millennials who demanded everything to be instant. The online market is not always good because there are many problems caused by the online market, such as quality goods fraud, cybercrime cases such as online account hijacking, goods security that is not guaranteed in the shipping process, and many others. The various problems posed by the online market are caused by a lack of direct interaction with the product or seller, so it can be concluded that the market still requires physical form.The method used to answer this issue begins with the process of collecting data on millennial habits and the issues that arise are mainly due to market developments. Then the matrix method is used to connect the data that has been collected until the results are obtained with diverse answers. Lastly, various massing experiments and concepts were carried out to create more options and develop more designs. Through this method the results are in the form of interactive programs that provide a different experience for the millennials so that the millennials will be interested in experiencing the space formed by the millennial market. The design experiment method also produces a form that gives identity to the environment around the site that lacks landmarks. The conclusion of this project is the Millennial Market: